Methylprednisolone Pulses in Hospitalized COVID-19 Patients Without Respiratory Failure: A Randomized Controlled Trial - Les, Iñigo; Loureiro-Amigo, Jose; Capdevila, Ferran; Oriol, Isabel; Elejalde, Iñaki; Aranda-Lobo, Judit; Modesto, Joao; Güell-Farré, Elena; García, Ruth; Murgadella-Sancho, Anna; Anniccherico, Javier; Martín-Fernández, Miguel; et al. (Frontiers in Medicine, 2022)
Background: Corticosteroids are the cornerstone of the treatment of patients with COVID-19 admitted to hospital. However, whether corticosteroids can prevent respiratory worsening in hospitalized COVID-19 patients without oxygen requirements is currently unknown. Aims: To assess the efficacy of methylprednisolone pulses (MPP) in hospitalized COVID-19 patients with increased levels of inflammatory markers not requiring oxygen at baseline. Methods: Multicenter, parallel, randomized, double-blind, placebo-controlled trial conducted in Spain. Patients admitted for confirmed SARS-CoV-2 pneumonia with raised inflammatory markers (C-reactive protein >60 mg/L, interleukin 6 >40 pg/ml, or ferritin >1000 µg/L) but without respiratory failure after the first week of symptom onset were randomized to receive a three-day course of intravenous MPP (120 mg/day) or placebo. The primary outcome was treatment failure at 14 days, a composite variable including mortality, the need for ICU admission or mechanical ventilation, and clinical worsening, this last parameter defined as a PaO2/FiO2 ratio below 300; or a 15% decrease in the PaO2 from baseline, together with an increase in inflammatory markers or radiological progression. If clinical worsening occurred, patients received tocilizumab and unmasked corticosteroids. The secondary outcomes were 28-day mortality, adverse events, need for ICU admission or high-flow oxygen, length of hospital stay, SARS CoV-2 clearance, and changes in laboratory parameters. Results: A total of 72 patients were randomized and 71 patients were analyzed (34 in the MPP group and 37 in the placebo group). Twenty patients presented with treatment failure (29.4% in the MPP group vs. 27.0% in the placebo group, p=0.82), with no differences regarding the time to treatment failure between groups. There were no cases of death or mechanical ventilation requirements at 14 days post-randomization. The secondary outcomes were similar in MPP and placebo groups. Conclusions: A three-day course of MPP after the first week of disease onset did not prevent respiratory deterioration in hospitalized COVID-19 patients with an inflammatory phenotype who did not require oxygen. Clinical Trial Registration: ClinicalTrials.gov, ClinicalTrials.gov Identifier: NCT04438980. EudraCT.ema.europa.eu, EudraCT registration number: 2020-001827-15.